Relationship Between Farmer’s Characteristics with the Motivation of Goat Milking in the Girikerto Village Turi District Sleman Regency - Siti Andarwati; Trisakti Haryadi; Budi Guntoro; Endang Sulastri; R. Ahmad Romadhoni Surya Putra; Gunawan Gunawan (Buletin Peternakan, 2018)
This research aimed to determine the relationship between farmer characteristics including age, education level, farming experience, side income, number of dependent family member, and farmer's business scale with the motivation of goat milking in Girikerto Village, Turi District, Sleman Regency. The type of this research was quantitative explanatory, that was the type of research explaining the nature of the relationship and examining the relationship between farmer characteristics with milking motivation. The research method used a household survey of farmers with the help of questionnaires. The number of respondent’s sample used was 56 goat farmers with provisions using the Slovin formula. Sampling technique used Simple Random Sampling. Data were analyzed by Product Moment correlation. The results showed that the variables of age, farming experience, and business scale had a significant relationship with the motivation of goat milking, while the variables of education, side job and a number of dependents had no significant relationship with the motivation of milking. Farmer’s motivation to milk goats could be increased in line with increasing the age and experience of farmers. The motivation of milking goats could also be increased by increasing the number of livestock ownership, especially the ownership of lactating goats.